Enhanced grain growth in lead-free (1-x)(Na0.5Bi0.5)TiO3- XAgNbO3solid solution ceramics - J. Y Y Wong (2018)
The lead-free (1-x)(Na0.5Bi0.5)TiO3- xAgNbO3(x = 0.00-0.15) ceramics were synthesized by solid state reaction. Anomaly large grain growth was observed by scanning electron microscopy with an average grain size reaching 90 μm for x = 0.02. The incorporation of AgNbO3into (Na0.5Bi0.5) TiO3led to highly dense ceramics without the addition of binder or sintering aid. The ceramics are slightly deficient in bismuth on the surface, which caused the formation of Na2Ti6O13whiskers. These whiskers can be removed by polishing for subsequent piezoelectric and ferroelectric characterizations.